2021
DOI: 10.1016/j.asmr.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Online Rehabilitation Protocols for Medial Patellofemoral Ligament Reconstruction With and Without Tibial Tubercle Osteotomy Are Variable Among Institutions

Abstract: Purpose: To compare and contrast the various rehabilitation protocols for medial patellofemoral ligament (MPFL) reconstruction and MPFL reconstruction plus tibial tubercle osteotomy (TTO) published online by academic orthopaedic surgery residency programs and private practice institutions throughout the United States. Methods: We performed a systematic electronic search of MPFL reconstruction rehabilitation protocols in academic orthopaedic surgery residency programs in the United States using Google's search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although it is important to carefully manage patient expectations regarding the timing of return to sport, this metric has been underreported in the literature [17]. One contributing factor could be the wide range of rehabilitation protocols for MPFLR—recent systematic reviews of postoperative protocols have found a wide range of recommendations regarding appropriate return to sport timing [34, 35]. This study highlights the need to refine and synthesize postoperative management for MPFLR with and without TTO.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is important to carefully manage patient expectations regarding the timing of return to sport, this metric has been underreported in the literature [17]. One contributing factor could be the wide range of rehabilitation protocols for MPFLR—recent systematic reviews of postoperative protocols have found a wide range of recommendations regarding appropriate return to sport timing [34, 35]. This study highlights the need to refine and synthesize postoperative management for MPFLR with and without TTO.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated 38 publicly available protocols, and only 13 of the 38 protocols (34.2%) included specific strength or functional testing guidelines for criteria to RTS. 28 Without clearly established return-to-play guidelines, athletes may be returning to sport with functional deficits that may increase injury risk or decrease ability to resume prior level of sport. Currently, RTS guidelines are most commonly seen within ACL literature.…”
Section: Functional Testing and Return To Sportmentioning
confidence: 99%